Strong Exciton–Plasmon Coupling in a WS2 Monolayer on Au Film Hybrid Structures Mediated by Liquid Ga Nanoparticles - Deng, Fu; Liu, Hongfeng; Xu, Lei; Lan, Sheng; Miroshnichenko, Andrey E. (Laser & photonics reviews, 2020)
Realizing and manipulating strong light–matter coupling in 2D monolayer semiconductors is of paramount importance in the development of novel photonic devices. Here, it is revealed by numerical simulation that strong coupling between the excitons in a WS2 monolayer and the surface plasmon polaritons propagating on the surface of a thin Au film can be realized when the surface plasmon polaritons are generated via the Kretschmann–Raether configuration. The use of liquid Ga nanoparticles, which exhibit broad scattering spectra in visible light, is proposed to identify the strong exciton–plasmon coupling. It is demonstrated numerically and experimentally that the exciton–plasmon coupling strength, which is manifested in Rabi splitting, can be further enhanced by the in‐plane localization of the electric field provided by liquid Ga nanoparticles. Anti‐crossing of the scattering spectra can be observed by tuning the angle of the incident light and Rabi splitting exceeding 120 meV can be obtained. The results open new horizons for realizing strong exciton‐plasmon coupling in hybrid structures composed of monolayer semiconductors and thin metal films and pave the way for the practical applications of strong light–matter interaction in nanoscale photonic devices. Strong coupling between the excitons in a WS2 monolayer and the surface plasmon polaritons propagating on the surface of a thin Au film is revealed numerically. A stronger exciton–plasmon coupling is demonstrated experimentally in a nanocavity formed by a liquid Ga nanoparticle and a thin Au film with an embedded WS2 monolayer.